Nutritional Ketoacidosis During Incremental Exercise in Healthy Athletes - Dearlove, David J.; Faull, Olivia K.; Rolls, Edward; Clarke, Kieran; Cox, Pete J. (Frontiers in Physiology, 2019)
Purpose Ketosis, achieved through ingestion of ketone esters, may influence endurance exercise capacity by altering substrate metabolism. However, the effects of ketone consumption on acid-base status and subsequent metabolic and respiratory compensations are poorly described. Methods Twelve athletically trained individuals completed an incremental bicycle ergometer exercise test to exhaustion following the consumption of either a ketone ester ((R)-3-hydroxybutyrate-(R)-1,3-butanediol) or a taste-matched control drink (bitter flavoured water), in a blinded, cross-over study. Respiratory gases and arterialised blood gas samples were taken at rest and at regular intervals during exercise. Results Ketone ester consumption increased blood d-β-hydroxybutyrate concentration from 0.2 mM/L to 3.7 mM/L (p<0.01), causing significant falls versus control in blood pH to 7.37 and bicarbonate to 18.5 mM/L before exercise. To compensate for ketoacidosis, minute ventilation was modestly increased (p<0.05) with non-linearity in the ventilatory response to exercise (ventilatory threshold) occurring at a 22 W lower workload (p<0.05). Blood pH and bicarbonate concentrations were the same at maximal exercise intensities. There was no difference in exercise performance having consumed the ketone ester or control drink. Conclusion Athletes compensated for the greater acid load caused by ketone ester ingestion by elevating minute ventilation and earlier hyperventilation during incremental exercise.